Pengaruh Keterhubungan Sosial Dan Citra Destinasi Wisata Tersembunyi Terhadap Niat Kunjung Wisata Melalui Rasa Takut Tertinggal Pada Mahasiswa - Mohamad Ridwan Abadi; Harmanda Berima Putra (Jurnal Akuntansi, Ekonomi dan Manajemen Bisnis, 2025)
A person's intention to take action or make decisions will be influenced by many factors, both from within themselves and external factors. The intention to visit among students will be influenced by social connectivity and the image of hidden tourist destinations. The purpose of this research is to analyze the effect of social connectivity and the image of hidden tourist destinations on the intention to visit tourism through the fear of missing out. The sample of this study consists of students from the Faculty of Economics and Business at Stikubank University. Data collection techniques used a questionnaire distributed via Google Forms. Data analysis techniques used SEM-PLS. The research results show that partially, social connection and destination image have a significant effect on the intention to visit. The fear of missing out mediates the effect of social connection on the intention to visit. However, the fear of missing out does not mediate the effect of the hidden destination image on the intention to visit.